Study of customer correlation bench test spectrum of charge air cooler of semi-trailer truck. (May 2022) - Han, Yu; Hong, Liang; Xie, Zhonghua; Zhang, Ce; Lin, Yier; Wang, Hongzhi
Highlights: Affecting CAC B10 life, thermal mechanical fatigue, gas pulse pressure fatigue and vibration fatigue are the main failure modes on the market. By collecting the fleet data of the user groups, the target driving path covering 95% of the actual use intensity of vehicle users is determined. The field load spectrum on the target driving path is collected, the fatigue damage is calculated and comparing it with the damage of the test bench in the laboratory, and the relevant bench test spectrum of the Charge Air Cooler of semi-trailer truck with B10 life is formulated. Abstract: In this paper, the bench test spectrum of charge air cooler of Semi-trailer truck, which is the bench test method of Charge Air Cooler reliability durability, and has the correlation with customer, is studied. Affecting CAC B10 life, thermal mechanical fatigue, gas pulse pressure fatigue and vibration fatigue are the main failure modes on the market. According to the principle that the users' damage is equal to the bench damage in the laboratory, the durability assessment test method of Charge Air Cooler on the bench in the laboratory is established. By collecting the fleet data of the user groups, the target driving path covering 95% of the actual use intensity of vehicle users is determined. The field load spectrum on the target driving path is collected, the fatigue damage is calculated and comparing it with the damage of the test bench in the laboratory, and the relevant bench test spectrum of the Charge Air Cooler of semi-trailer truck with B10 life is formulated. The practical application results show that this method can accurately predict the potential failures of the Charge Air Cooler of semi-trailer truck. And product development cycle is effectively shortened.